An assessment of the mobile banking application of Maybank Philippines, Inc. - Dequito, Catherine Ann A.; Cruz, Prof. Edison; Maybank Philippines, Inc. (Quezon City University of the Philippines Diliman, 2016)
With mobile phones becoming a necessity and an important piece of technology to consumers, banks are driven to explore an alternative channel to its customers. Accessibility, 24 by 7 availability, and convenience are only few of the many benefits that the mobile banking
application is offering to its clients. For the organization, this alternative channel entails wider banking coverage, at the same time, reduced cost as it departs from the traditional brick-and-mortar branch banking and focuses instead on improved customer experience.

Maybank Philippines, Inc. is one those organizations that leveraged on the growing demand for mobile applications. As a strategy, the Maybank Group came up with a regionalized mobile banking platform for its customers in Malaysia, Indonesia, Singapore and Philippines. It aims to
standardize the ‘look and feel’ of the user interface and work on an integrated platform and continuously adopt the speed-to-market approach.

This study analyzed the implementation of Maybank Philippines’s Mobile Banking application known as Maybank PH app. The study aims to look into the project implementation of the mobile application in MPI. In doing
so, it highlights the features of the technology, the factors that drove its successful implementation and the role of technology in the competitive strategy of the organization. Also, it seeks to understand how clients view the application to improve customer service delivery. Using the results of the survey, the organization can look into features that needs improvement and strengthen those that are deemed useful to the users.

The work of Statnikova (based on Kwon and Zmud’s IS Implementation Stages) and the Technology-Organization-Environment framework of Tornatzky and Fleischer are the main foundation of the framework used
for this study. This was used to relate how the various stages of IT implementations are affected by technology, organizational and environmental factors. For the acceptance stage, Davis’ Technology Acceptance Model (TAM) was used due to the impact of perceived ease
of use and perceived usefulness in the usage of the application.

To be able to answer the research questions, the descriptive research method was used. Qualitative and quantitative approach were combined by using document review for functionalities and project implementation
and survey to Maybank PH app users to understand client behavior and perception towards the mobile application. Results were tallied and reported in the results section in the form of frequency distribution.

The Maybank PH application offers the standard banking functionalities such as account inquiry, bills payment, fund transfer and prepaid loading. Its architecture is built on a ‘build once, deploy many’ principle, incorporating the best practice on multi-layer set-up and enterprise architecture principles. It follows the Maybank Group’s Enterprise Architecture standards and security. The security features of the application incorporates the two-factor authentication in its user authentication. The use of security image and passphrase further strengthens the login via username and password. A transaction authentication code (TAC) is also used for critical transactions.

The implementation of the project followed the Systems Development Lifecycle (SDLC) which is also implemented across the Maybank Group. It follows strict adherence to documentations and puts value to governance
process. The organizational climate of MPI and Maybank Group as a whole encourages innovation. Management commitment is obtained from the start of the project. They are also involved throughout the project duration as well as the various governance units such as Audit, Data
Governance, IT Security, Enterprise Architect, Compliance and Operational Risk. The user’s involvement in the project is critical in ensuring its success as they will be one supporting the system and marketing it to the clients.

The results of the survey reflected a positive response from the thirty-five respondents based on questions on compatibility, perceived usefulness, perceived ease of use and attitude towards the new technology. The sample was a mix of male and female with ages within the range of 21 to 30 years old and average gross monthly income of PhP 20,001 to PhP 40,000. Majority of the respondents are relatively new account holders with relationship with the bank for only one to three years. Bank channels
used mostly is internet banking, while mobile banking is used only as needed. Most common feature used are account inquiry, bills payment and fund transfer, which are also the features that the respondents liked most. Some respondents also suggested additional features to incorporate in the mobile app such as transfer to anyone, finger print logon, transfer to other Philippine banks, foreign exchange dashboard for other currencies, additional merchant, and linkage to credit card as well as improvements in the performance. Overall, the Maybank PH app received a rating of 4 out for 5 from the surveyed respondents.

In conclusion, technology, organization and environment factors mentioned in this study affects the implementation and use of the Maybank PH app at various degrees. It can be concluded that the 10 Maybank PH app is acceptable to the sample surveyed based on the positive responses when asked regarding their feedback on the ease of
use and usefulness of the application.

The implementation of the mobile banking application is considered as successful, however, to be fully accepted, the organization must look into acceptance of its users as measure of the initiative’s success. Also, being a mobile application, continuous fixes and improvements are necessary for users to patronize the application. This does not pertain only to functionalities, but also in the security and marketing tools. Recommendations are made to increase the sample size and adopt a more comprehensive method of assessment of this study. A survey can be incorporated in the Maybank PH app to obtain feedback from its users. At the same time, the possibility of including a post-implementation
acceptance metrics as part of the organization’s method to evaluate projects will be useful in measuring the benefits of the projects against investment.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Banks and banking, Mobile -- Philippines